Pengembangan Alat Pencacah Pakan Ternak Serbaguna untuk Meningkatkan Produktivitas Peternakan di Desa Lido Kecamatan Belo Kabupaten Bima - Rahmawati; Imaduddin, M. Asad; Jufrin, Jufrin; Bulqis, Bulqis; Teibang, Dopu (Swadaya: Jurnal Pengabdian Masyarakat, 2024)
Purpose: Livestock waste can pollute the environment and produce methane gas, contributing to climate change and spreading diseases if not properly managed. Effective waste management is crucial for safety and health in livestock environments and nearby communities. Cattle farming in Lido Belo Village has substantial economic potential, offering a value chain that includes raising livestock, producing organic fertilizer, and marketing products to boost local income. It also supports food security and economic diversification, creating jobs, enhancing skills, and improving community welfare. Methodology: The community service program uses field visits to understand the conditions and challenges faced by local livestock groups. Findings:The 'Talaga Na'e' cattle group struggles with converting cow dung into economical manure, addressed by creating a manure mixer to improve waste processing and income. The 'Mandiri' cattle group faces feed chopping inefficiencies, resolved by developing a feed chopper to enhance productivity and focus on livestock care.